Characterization of the microbial community composition in Italian Cinta Senese sausages dry-fermented with natural extracts as alternatives to sodium nitrite. (August 2020) - Pini, Francesco; Aquilani, Chiara; Giovannetti, Luciana; Viti, Carlo; Pugliese, Carolina
Abstract: Nitrite is widely used in meat products as a multifunctional additive, combining flavour and colour properties with antioxidant and antimicrobial effects. However, nitrite may form reaction products (i.e., nitrosamine) that are potentially carcinogenic to humans. The meat industry, in response to consumers' demands for nitrite-free products, is seeking natural alternatives to nitrite, such as plant-based extracts. Three types of dry-fermented sausages were manufactured: NIT, containing 30 ppm of sodium nitrite; GSE, containing grape seed extract and olive pomace hydroxytyrosol; and CHE, containing chestnut extract and olive pomace hydroxytyrosol. Next-generation sequencing (NGS) was used to analyse microbial consortia, which were correlated with physical and chemical parameters. The prokaryotic community composition was similar among treatments, with a high relative abundance of Staphylococcus xylosus and Lactobacillus sakei, collectively accounting for 87% of the total community. However, significant differences were observed in both operational taxonomic unit (OTU) presence/absence and relative abundance. Ten genera varied in abundance between treatments. The increase in Lactobacillaceae in CHE may explain the reduced pH levels detected in these samples. In conclusion, NGS analysis showed that the prokaryotic community composition was similar in GSE and NIT, while CHE varied in both the composition and relative abundance of different taxa. Highlights: Grape seed and chestnut extracts reduced pH levels in Italian Cinta Senese sausages, probably due to increased Lactobacillaceae presence. Staphylococcus xylosus and Lactobacillus sakei were the most represented species in dry-fermented sausages microbiota. The natural extracts did not drastically alter the prokaryotic community. In nitrite-free samples, a relatively lower abundance of the Photobacterium genus was detected.